Peran Pemerintah Daerah dalam Mewujudkan Kepastian Hukum Surat Keterangan Tanah Di Kabupaten Belitung - Nur Aini; M. Sudirman (Lembaga Pengembangan Kinerja Dosen, 2024)
The many land problems require a significant role from the regional government to create legal certainty regarding the existence of Land Certificates in Belitung Regency. The research method used in this writing is a normative juridical research method using a Statutory Approach and a Conceptual Approach. The data used is secondary data consisting of primary legal materials, secondary legal materials and tertiary legal materials. For data analysis using Legal Interpretation Techniques and Legal Construction Techniques. The results of this research show that until now there has been no regulation or legal product governing Land Certificates in Belitung Regency, so clear regulations are needed regarding the existence of these Land Certificates in order to create legal certainty and reduce land problems and disputes.